Estudo da qualidade ambiental do reservatório pentecoste por meio do índice de estado trófico modificado - Oliveira, Rafael Reis Alencar (2009)
The growing concern with the maintenance of the environmental quality of water sources in Ceará refers to the intense degradation of reservoir through the eutrophication phenomenon, which results in an accelerated enrichment of nutrients from, particularly, the release of effluents from rural, urban and industrial zones. The fact of water presents as the main factor limiting of development and improvement of welfare of people in Semi- Arid, naturally insufficient in their water availability, marks the importance of the better understanding of this phenomenon in order to keep the possible uses of these water sources, as for any kind of use, there is a standard which should be respect. This study intended to examine the behavior of the indicators of water quality at Pentecoste reservoir, Ceará State, seeking to identify the main changes in their trophic levels using the method of calculating the Trophic State Index Modified. As a perspective of analysis, is used the spatial and temporal variability of limnological information available for the years 2001 to 2008. The result of this analysis showed that the levels of total phosphorus, soluble orthophosphate and chlorophyll a remained high, indicating even the tendency of the weir Pentecoste high eutrophication. The behavior of these indicators was related to hydrological processes of the reservoir, particularly the rainfall regime, with strongly determinate the variability of water quality during the study period, indicating even the years 2004 and 2006 as critical. For the classification of the trophic estate, the use of indicators was well suited because of the good relationship of cause and effect between them, and the nitrogen and phosphorus indicated the total phosphorus as a limiting phytoplankton development in the reservoir. The characterization of the dam on Pentecoste IETM determined the predominance of eutrophic state, with a slight tendency of hypereutrophic, especially in periods of higher rainfall. The relationship of temporal and spatial distribution of rainfall regime with the trend of trophic state showed the impact of the rain water drainage systems as a catalyst in the process of eutrophication, emphasizing, in this sense, that the forms of use and occupancy of the areas surrounding the reservoir may interfere directly in the quality of it. As the spatial dispersion of IETM concludes that there is a trend of deterioration of water quality in the vicinity of dam and the dam and the city of Pentecoste, that pattern changed considerably for the rainy periods. Finally, the study showed that both the frequency and intensity as the sample distribution of collections can directly influence the classification of the trophic state of a water body and the understanding of hydrological processes in this reservoir.